DEVELOPMENT OF AN APPROACH TO DETERMINATION OF COUPLING QUALITIES OF ROAD COVERING USING WEATHER-CLIMATE FACTOR - Shevtsova, Anastasia; Novikov, Alexander (Journal of Applied Engineering Science, 2020)
Assessing the grip of the road surface is an extremely important task both in the field of traffic management, and in the field of investigation and examination of traffic accidents. The coupling quality of the road surface is fully ensured by the grip coefficient, which is subject to constant monitoring in order to ensure road safety. There are a large number of methods for determining the magnitude of the grip coefficient. In their study, the authors propose an improved approach for determining the investigated value using the weather and climate factor. Previously, a group of researchers in the course of scientific research determined the dependence of the grip coefficient on the temperature of the road surface, as a result of mathematical analysis, the authors obtained a dependence that allows to determine the studied value by air temperature and the condition of the road surface (presence of precipitation). The performed experiment allowed us to test the obtained dependence within the framework of the object of study and to make a comparative assessment of the results obtained with the data obtained using the road laboratory.
Keywords: coefficient of friction; test methods; mathematical analysis; dependence; weather and climate conditions residues; information and logical model of the process; modeling of technological process